Insulated molecular wires: Synthesis of conjugated polyrotaxanes by Suzuki coupling in water - Taylor, P; O'Connell, M; McNeill, L; Hall, M; Aplin, RT; Anderson, H (2000)
Poly-para-phenylene polyrotaxane 1 is the first conjugated polyrotaxane. The napthalene end groups prevent the β-cyclodextrin rings from slipping off the conjugated backbone in solution. The matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrum shows a series of oligomers, up to a [10]rotaxane.